Alternatively spliced transcripts of the Drosophila tramtrack gene encode zinc finger proteins with distinct DNA binding specificities. - Read, D (1992)
A protein present in nuclear extracts of Drosophila embryos binds multiple sites in the promoter and genetically defined autoregulatory element of the pair-rule gene even-skipped (eve). We reported here the isolation of a cDNA encoding this binding activity, the sequence of which identifies it as the 69 kDa zinc finger tramtrack (ttk) protein. As ttk was previously implicated in controlling the expression of another pair-rule gene, fushi tarazu (ftz), our findings suggest that ttk plays a role in the regulation of at least two developmentally important genes. An additional ttk-related cDNA clone was isolated which gives rise to an 88 kDa protein with an alternative set of zinc fingers having a DNA binding specificity distinct from that of the 69 kDa protein. Both proteins were shown to be encoded by the ttk gene through alternative splicing, providing the first example of the use of this mechanism to generate related proteins with distinct DNA binding specificities. Whole mount in situ hybridization analysis revealed different patterns of embryonic expression of the two ttk mRNA isoforms.